Antimicrobial resistance: Past, present, and way forward - Ramashankar Rath; Pradip Kharya; Aroop Mohanty; Anil R. Koparkar; Anand M. Dixit; Hari Shanker Joshi; Vivek Hada (Indian Journal of Community Medicine)
Antimicrobial resistance (AMR) is one of the important public health problems across the world. Low-middle-income countries are facing the problem more strongly than the high-income countries. AMR is likely to increase the cost of healthcare expenditure over the years. Over the years, various factors like unprecedented use of the antimicrobials in humans, animals, and plants or vegetations and over-the-counter sell of the antibiotics without prescription along with poor sanitation have led to the development and transfer of AMR across the various animal groups. To tackle the issue of the AMR in the country, the Government of India has launched the national program for containment of AMR in 2013 with six identified domains. A containment plan is currently being executed but yet to achieve the full extent as intended. Programmatic consideration aimed to address all the components of AMR development of AMR and its transmission across all levels of health care.